2009
DOI: 10.1038/onc.2009.318
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression and signaling in drug-induced cellular senescence

Abstract: Cellular senescence guards against cancer and modulates aging; however, the underlying mechanisms remain poorly understood. Here, we show that genotoxic drugs capable of inducing premature senescence in normal and cancer cells, such as 5-bromo-2 0 -deoxyuridine (BrdU), distamycin A (DMA), aphidicolin and hydroxyurea, persistently activate Janus kinase-signal transducer and activator of transcription (JAK/STAT) signaling and expression of interferon-stimulated genes (ISGs), such as MX1, OAS, ISG15, STAT1, PML, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
95
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 49 publications
10
95
0
Order By: Relevance
“…Some reports attribute the expression of IFN-related genes to cellular senescence [39,40]. To investigate this possibility, we measured the activity of β-galactosidase, a senescence marker, in BRCA2 −/− and BRCA2 +/+ cells.…”
Section: Expression Of Ifn-related Genes Is Up-regulated In Brca2 Knomentioning
confidence: 99%
“…Some reports attribute the expression of IFN-related genes to cellular senescence [39,40]. To investigate this possibility, we measured the activity of β-galactosidase, a senescence marker, in BRCA2 −/− and BRCA2 +/+ cells.…”
Section: Expression Of Ifn-related Genes Is Up-regulated In Brca2 Knomentioning
confidence: 99%
“…Many stimuli can trigger senescence, including telomere shortening (replicative senescence), oncogene activation, and DNA damage. The cellular program executing senescence is dependent on DNA damage checkpoints and mitogenic signaling networks including STAT1, RAS, and PI3K (7)(8)(9). Senescence is considered a tumor-suppressive mechanism in many malignancies (10), and the appreciation that many chemotherapeutic agents induce senescence has prompted a resurgence of interest in prosenescent anti-cancer therapies.…”
mentioning
confidence: 99%
“…Expression of PML is stimulated by interferons of type I and II (9 -12), which are produced during cellular responses to viral infection (for review, see Ref. 56) and some genotoxic insults (32,33). Response of PML to both types of interferons is mediated via transcription factors STAT1 and STAT2 (27), and it is suppressed by inhibitors of histone deacetylases (47).…”
Section: Discussionmentioning
confidence: 99%
“…5 As mentioned above, the common denominator of these two types of stresses (viral and genotoxic) is activation of a complex cytokine network including induction and secretion of IL6 (26, 32, 76 -78). In our previous work we showed that both JAK/STAT1/2 and JAK/ STAT3 signaling is involved in stress-induced PML gene transcription (32,33). One of the key questions raised by those studies was which other cytokines in addition to interferons induce PML (13).…”
Section: Il6-stat3 Regulates Pml Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation